Development of composite outcomes for individual patient data (IPD) meta‐analysis on the effects of diet and lifestyle in pregnancy: a Delphi survey. (January 2016) - Rogozinska, E; D'Amico, MI; Khan, KS; Cecatti, JG; Teede, H; Yeo, S; Vinter, CA; Rayanagoudar, G; Barakat, R; Perales, M; Dodd, JM; Devlieger, R; et al.
Abstract : Objective: To develop maternal, fetal, and neonatal composite outcomes relevant to the evaluation of diet and lifestyle interventions in pregnancy by individual patient data (IPD) meta‐analysis. Design: Delphi survey. Setting: The International Weight Management in Pregnancy (i–WIP) collaborative network. Sample Twenty‐six researchers from the i–WIP collaborative network from 11 countries. Methods: A two‐generational Delphi survey involving members of the i–WIP collaborative network (26 members in 11 countries) was undertaken to prioritise the individual outcomes for their importance in clinical care. The final components of the composite outcomes were identified using pre‐specified criteria. Main outcome measures: Composite outcomes considered to be important for the evaluation of the effect of diet and lifestyle in pregnancy. Results: Of the 36 maternal outcomes, nine were prioritised and the following were included in the final composite: pre‐eclampsia or pregnancy‐induced hypertension, gestational diabetes mellitus (GDM), elective or emergency caesarean section, and preterm delivery. Of the 27 fetal and neonatal outcomes, nine were further evaluated, with the final composite consisting of intrauterine death, small for gestational age, large for gestational age, and admission to a neonatal intensive care unit (NICU). Conclusions: Our work has identified the components of maternal, fetal, and neonatal composite outcomes required for the assessment of diet and lifestyle interventions in pregnancy by IPD meta‐analysis. Tweetable abstract: Composite outcomes in IPD meta‐analysis on diet and lifestyle in pregnancy. Tweetable abstract: Composite outcomes in IPD meta‐analysis on diet and lifestyle in pregnancy. This article includes Author Insights, a video abstract available athttps://vimeo.com/148890226